Investigation of the pathogenicity of Rubella virus for the central nervous system - Domegan, Lisa Mary (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2002)
Rubella virus (RV) is the cause of a mild self limiting disease, known as German measles, which predominates during childhood. It is however the devastating teratogenic effects of this virus that are of most concern. Rare neurological sequelae following RV infection include encephalitis and progressive rubella panencephalitis (PRP). Rubella is endemic throughout the world, causing epidemics that occur at irregular intervals.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin